(untitled) (Vietnam Journal of Community Medicine, 2026)
1.Objective: To evaluate the clinical and paraclinical characteristics as well as the early surgical outcomes of patients with aortic valve stenosis treated at Hanoi Medical University Hospital during the period 2021–2024. • Methods: A descriptive study was conducted on patients diagnosed with aortic valve stenosis who underwent surgery at Hanoi Medical University Hospital from January 2021 to December 2024. 3.Results: The study included 40 patients with a mean age of 63.7 ± 8.2 years; males accounted for 67.5%. The main symptom was chest pain (65%). NYHA class II before surgery was observed in 85%. All patients (100%) had a systolic murmur at the aortic valve area. Preoperative echocardiography showed left ventricular enlargement with LVM(g) 240.2 ± 75.2, and most patients had preserved left ventricular function, with 80% having EF >50%. All patients presented with severe aortic valve stenosis and ascending aortic dilatation, with a mean transvalvular gradient of 62.5 ± 16.1 and ascending aortic diameter of 40.5 ± 5.2 mm. A bicuspid aortic valve abnormality was found in 35 patients (87.5%). Surgical procedures included 17.5% with ascending aortic replacement, 40% with ascending aortic wrapping, and 7.5% with mitral valve repair using an annuloplasty ring. Postoperatively, 95% of patients were discharged with good outcomes; one patient died due to intraoperative Stanford type A aortic dissection leading to multiorgan failure, and one required reoperation for sternal reconstruction due to sternal dehiscence. 4.Conclusion: Aortic valve stenosis is predominantly observed in the elderly population, manifesting with a heterogeneous spectrum of cardiac symptoms, ascending aortic involvement, and comorbidity-related conditions. Surgical management primarily consists of aortic valve replacement combined with appropriate intervention on the ascending aorta, achieving a high rate of procedural success.